Gestão e trabalho: a relação entre a saúde e o trabalho de gerentes da atenção básica à saúde - Rossini, Victor Camargo (2023)
This study aims to comprehensively understand the relationship between health and work among managers of Family Health Units (FHU). This purpose is further divided into specific objectives, starting by examining how these managers organize their work activities to maintain their health; understanding the nature of managerial work; investigating their understanding of health and work; identifying prevalent patterns of illness and their causes; exploring how managers balance work with their personal lives. Ten managers from a health district located in a capital city in the Northeast of Brazil participated in this study. The theoretical framework upon which this research is based is Ergology. As for the methodology, this work can be characterized as a case study, where the following instruments were used: a semi-structured questionnaire, with questions about social and professional data, and a semi-structured interview. The data analysis was conducted using content analysis as an analytical method that categorizes and complements the data, with the aim of obtaining a more meaningful interpretation. It was found that the managers have a complex and multifaceted job. Each of them employs different strategies to maintain their health at work, such as effective teamwork, separating personal and professional aspects, and achieving satisfactory results in solving the issues faced by the users of the FHUs they oversee. It was also noticed that the lack of recognition for their efforts and the inconsistencies in the work environment, whether from users or the team, result in difficulties in managing their lives and work. The study also addressed gender issues, as all the interviewees were women, and there were connections between their profession, remuneration, and their role in caregiving functions. Furthermore, it was observed that these managers demonstrated high satisfaction and feel healthy in their roles within these units. Recognition for their work, salary adjustments, and improvements in issues like infrastructure and the team are crucial aspects in ensuring the health of these managers, given that the question arose at the end of the research regarding the possibility of maintaining their health at work in light of these persisting problems.